A rare case of full neurological recovery from severe nonexertional heatstroke during a bedrock bath. (31st May 2018) - Sagisaka, Shogo; Tamune, Hidetaka; Shimizu, Keiki; Kashiyama, Tetsuya
Abstract: We report a rare case of full neurological recovery in a 77‐year‐old woman with an initial Glasgow Coma Scale of 3 while taking a bedrock bath. Severe heatstroke was quickly diagnosed, and intensive treatment was immediately provided. Laboratory data showed multi‐organ failure, and her electroencephalogram showed very low amplitude, indicating a poor prognosis; however, she gradually recovered consciousness, and her electroencephalogram normalized, showing a Glasgow Coma Scale of 15 at discharge. This case demonstrated that physicians should pay careful attention when withholding treatment from a patient with severe heatstroke accompanied by a poor initial electroencephalogram result and laboratory data. Abstract : We report a rare case of 77‐year‐old woman diagnosed as severe heatstroke caused by bedrock bath. Although her initial electroencephalogram indicated very poor prognosis, she was successfully extubated and discharged with no neurological dysfunction.